PENINGKATAN KINERJA GURU MI DI KECAMATAN JUMO TEMANGGUNG DALAM PENILAIAN BERBASIS KELAS MELALUI SUPERVISI KLINIS - Makhsun, Nur (Kopertais Wilayah X Jawa Tengah, 2020)
The purpose of this supervisory action research (PTKp) was to determine the performance improvement of MI teachers at Madrasah Ibtidaiyah in Jumo District, Temanggung Regency in carrying out class-based assessments through clinical supervision. In this supervisory action research (PTKp) was carried out in 3 cycles, from the results of the actions taken, it was proven to improve teacher performance by achieving ideal standards. to III 86.76%. The results of this action research indicate that coaching through clinical supervision of supervisors can improve teacher performance in carrying out class-based assessments with completeness reaching 100%.